Evidence for genetic heterogeneity in tuberous sclerosis. Issue 8 (August 1989) - Sampson, J R; Yates, J R; Pirrit, L A; Fleury, P; Winship, I; Beighton, P; Connor, J M
Abstract : The question of genetic heterogeneity in tuberous sclerosis (TSC) was addressed by genetic linkage studies in eight affected families using nine polymorphic markers (EFD126.3, MCT136, ABO, ABL, AK1, and MCOA12 from distal 9q, and PBGD, MCT128.1, and 1CJ52.208M from distal 11q). The data as a whole supported a TSC locus on distal 9q, the peak lod score on multipoint analysis being 3.77 at 6 cM proximal to the Abelson oncogene locus (ABL). However, analysis of two point lod scores using the HOMOG programs showed significant evidence for genetic heterogeneity (p = 0.01), linkage to ABL being unlikely in one family. After exclusion of the unlinked family, multipoint analysis gave a peak lod score of 6.1 in the vicinity of ABL. The family unlinked to ABL showed no recombinants with two chromosome 11 probes, but was too small to provide significant evidence for linkage. Genetic heterogeneity in TSC will complicate efforts to clone the causative genes and severely limit the use of linked probes for carrier detection and prenatal diagnosis.